The Economic Value of Caregiving in Chile - Villalobos-Dintrans, P (Routledge, 2024)
Population aging will increase the demand for long-term care services. Many countries, including Chile, have not implemented comprehensive responses to address these demands, relying on informal care. This article aims to estimate the economic value of caregiving in Chile, contributing to filling a gap in the literature and the policy debate. Economic value is estimated using replacement and opportunity cost approaches using two nationally representative databases: one survey on time use (to estimate hours of caregiving) and one on socioeconomic characterization (to identify caregivers and wages). Regressions for the determinants of caregiving effort and wages in the formal labor market are used to calculate the market value of caregiving time. Results show that the yearly value of caregiving ranges between US$266 million (when assuming a wage equal to the minimum wage for all caregivers) and US$4,946 million (when replacing all caregivers with nurses), i.e. between 0.11% and 1.95% of the country’s gross domestic product. The analysis provides several estimations of the economic value of caregivers in Chile and, even considering these calculations can be underestimated, the results show the need to highlight and value the contribution of caregivers and implement policies to address the increase in long-term care needs in the country. © 2023 Taylor & Francis.